Letter to the editor: Conservative management of occult pneumothorax in mechanically ventilated patients—A systematic review and meta-analysis. Issue 6 (1st June 2022) - Borazjani, Roham; Sabetian, Golnar; Shams, Amir Hossein; Ahadi, Mahsa; Paydar, Shahram
Abstract : We suggest that patients with occult pneumothorax who are under mechanical ventilation could be monitored using lung ultrasound.